2022
DOI: 10.3389/fgene.2022.812449
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Structure Analysis of KCS Family Genes Suggest Their Reponding to Regulate Fiber Development in Long-Staple Cotton Under Salt-Alkaline Stress

Abstract: Plant 3-ketoacyl-CoA synthase (KCS) gene family catalyzed a β ketoacyl-CoA synthase, which was the rate-limiting enzyme for the synthesis of very long chain fatty acids (VLCFAs). Gossypium barbadense was well-known not only for high-quality fiber, which was perceived as a cultivated species of Gossypium. In this study, a total of 131 KCS genes were identified in four cotton species, there were 38, 44, 26, 23 KCS genes in the G. barbadense, the G. hirsutum, the G. arboreum and G. raimondii, respectively. The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…VLCFA is an important precursor substance for the synthesis of plant cuticle waxes. KCS family genes, which encode the key restriction enzyme in the VLCFA synthesis pathway, have been identified in various plant species [4,27,28]. In this study, 20 XsKCS genes were identified in the yellow horn genome (Table 1).…”
Section: Discussionmentioning
confidence: 83%
“…VLCFA is an important precursor substance for the synthesis of plant cuticle waxes. KCS family genes, which encode the key restriction enzyme in the VLCFA synthesis pathway, have been identified in various plant species [4,27,28]. In this study, 20 XsKCS genes were identified in the yellow horn genome (Table 1).…”
Section: Discussionmentioning
confidence: 83%
“…Glycerol-3-phosphate acyltransferase (GPAT), a key gene in glycerophospholipid metabolism, was increased 3–8-fold upon SLT (Figure S5D). The GPAT gene is associated with fatty acid unsaturation and plays a pivotal role in cold resistance in a number of plant species. , Plant 3-ketoacyl-CoA synthase (KCS), which is involved in the biosynthesis of very long chain fatty acids (VLCFAs), was increased 20-fold upon SLT stress training (Figure S5D). VLCFAs play important roles in biosynthesis of cuticular waxes, a hydrophobic film deposited on aerial tissue surfaces, and provides protection against pathogen infection .…”
Section: Resultsmentioning
confidence: 99%
“…From previous studies, we have learned that some genes play important roles in fatty acid regulation. Taking KCS16 in the core network as an example, KCS16 is a member of the 3-ketoacyl CoA synthase family involved in very-long-chain fatty acid (VLCFA, C > 20) biosynthesis [ 38 ]. This gene is highly expressed in siliques and also substantially in leaves and other organs [ 39 ], and the enzyme has no in vitro elongation activity toward C16–C20 substrates [ 40 ].…”
Section: Discussionmentioning
confidence: 99%